UNDERSTANDING SUCCESS ACCORDING TO CROWDFUNDING PROJECT’S INITIATORS - SILVA, Susana Costa e; VIEIRA, Ana Isabel Tavares (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0015 Over the past few years, a large number of projects related to entrepreneurship ideas have appeared daily in the media, due to the fact that they were sold as new solutions for companies or gave origin to new companies. These projects were mainly created by individuals who were students, unemployed persons or working people and, consequently, did not have a company of their own and, in most of the cases, also did not have the means to finance their idea. In some situations, the creation of a crowdfunding project presents itself as a convenient and riskless option for funding and this is frequently the reason why some project initiators decide to launch a campaign. The assessment of each campaign depends on the expectations of the project creator, who is in the best position to decide whether it was actually successful. Untangling how a project owner can assess the performance of its project is of major importance, namely when projects are launched by individuals who ultimately carry all the tasks involved in the initiative. This is a field of research within crowdfunding that remains, to the best of our knowledge, under researched. We propose a framework for the analysis of the success of these projects and we test it on six crowdfunding projects launched in Portugal. Our goal is to shed light to the factors that can be used by project creators in the assessment of the performance of their initiatives. JEL classification: O22